PD-Free Design of Insulation Systems: An Application to Laminated Busbars - Gian Carlo Montanari; Pasquale Cambareri (Applied Sciences)
The reliability of components of industrial electrical assets fed by power electronics might be at risk due to the type and extent of electrothermal stresses. The move of power electronics toward higher levels of voltage, switching frequency, slew rate, and specific power increases the risk of partial discharge inception and thus of accelerated extrinsic aging and premature failure. The reaction to this challenge is to embrace the concept of partial discharge-free (PD-free) design and operation. This paper presents a PD-free approach to the design of laminated busbars, considering both AC and DC insulation subsystems, and focusing on surface insulation. The availability of a recently proposed model to estimate the inception field is a key tool. The model is validated through PD measurements performed on a laminated busbar, using new automatic software that can identify the type of source generating PD. Combined with electric field calculations, the model provides estimates of the PD inception voltage which are almost coincident with the measurement results. Inception voltages in the order of 10 kV and 20 kV have been observed for AC and DC excitation, respectively. In the case of DC supply, tests at different ambient temperatures, 25 °C and 60 °C, indicate that the inception voltage does not change significantly with temperature. Disposability, scalability to any voltage/power, and capability to work, potentially, for any other type of insulation system, are interesting features of the proposed approach, which are discussed in the paper.